Magnetic resonance imaging correlates of neuronal degeneration of brain stem nuclei in Parkinson’s disease - Schwarz, Stefan Theodor (2016)
Parkinson’s disease (PD) is a progressive neurodegenerative disorder characterised by a loss of pigmented dopaminergic neurons in the substantia nigra (SN) pars compacta and loss of pigmented noradrenergic neurons in the locus coeruleus (LC). Diagnosing PD can be challenging, especially in the early stages particularly when the typical movement disorder symptoms such as tremor, rigidity, bradykinesia and postural instability are not easily identifiable. Despite well-established PD clinical diagnostic criteria there is a misdiagnosis rate of up to 15% by neurology specialists and 25 % by general practitioners. The only approved diagnostic test to confirm suspected PD in a tremulous patient is dopamine transporter single photon emission tomography (DaTScanTM). This test is costly (£800 – 1500 in the UK) and has limited geographical availability in the UK. It involves exposure to ionising radiation and can only be used to assess the integrity of the dopaminergic system. Therefore there is a strong need for better and more accessible diagnostic tests for PD. The aim of this thesis is to investigate the sensitivity and specificity of three different MRI techniques as potential biomarkers of PD. MRI at 3T field strength was used in this thesis to demonstrate PD pathology in the pigmented brain stem nuclei of SN, LC and the ventral tegmental area (VTA). The objective was to develop new, easily accessible and affordable disease markers to help clinicians to establish the correct diagnosis early.